To rewrite the expression \( 27^{1/2} \times 27^{1/4} \), you can use the property of exponents that states \( a^m \times a^n = a^{m+n} \).
So, we can combine the exponents:
\[ 27^{1/2} \times 27^{1/4} = 27^{(1/2 + 1/4)} \]
Next, we need to add the exponents \( 1/2 \) and \( 1/4 \). To do this, we find a common denominator, which is 4:
\[ 1/2 = 2/4 \] \[ 1/4 = 1/4 \]
Now we can add them:
\[ 1/2 + 1/4 = 2/4 + 1/4 = 3/4 \]
Thus, we have:
\[ 27^{1/2} \times 27^{1/4} = 27^{3/4} \]
So, the rewritten expression is:
\[ 27^{3/4} \]